Risks and opportunities of digital technologies in the school. Reflections about planning the teacher’s training - Patrizia Vayola (Formare, 2016)
Looking forward to the new intensive sessions of teacher training about the use of digital technologies promised by the Italian National plan for Digital school, this paper points out some risks to avoid and some opportunities to highlight. The aim is to ensure that teachers understand the value and the limits of the use of digital technologies in everyday didactics and are able to individuate the settings and the objectives in which technology supply actually results useful. I rischi e le opportunità del digitale a scuola. Spunti di riflessione per progettare la formazione dei docenti In vista delle nuove intensive tornate di formazione dei docenti all’uso delle tecnologie digitali promosse dall’attuazione del Piano Nazionale Scuola Digitale, l’articolo segnala alcuni rischi da evitare ed alcune opportunità da sottolineare per fare in modo che gli insegnanti comprendano valore e limiti dell’introduzione di questi strumenti nella didattica quotidiana e siano in grado di individuare gli ambiti e gli obiettivi per i quali può essere utile il loro apporto.